THE CONSENT DECREES IN THE BRAZILIAN CAPITAL MARKET - Chaves, Vinicius Figueiredo; Sertã Alexandre Folly Nogueira (PANORAMA OF BRAZILIAN LAW, 2018)
Supported by literature research, document and data collection, an approach concerning the legal regulation of capital market is carried out, starting from the review of the regulatory instrument known as consent decree (settlement). Its first step aims at the clarification of general notions about the roles and segments of capital market, followed by the presentation of the fundamental principles regarding the disciplined set of legal dispositions. In the sequence, some features of the Brazilian regulatory body, the Brazilian Securities and Exchange Commission (CVM), are presented, such as its functions and powers, focusing on the exam of the regulatory provisions contained in the sanctioning administrative process (SAP). In accordance with Article 11, § 5 of Law no 6.385/76, the rules issued by CVM, which govern PAS both in ordinary and in summary rites, prescribe that, once the defendant is summonned, the issuing of a warning to advert about the possibility to propose a term of commitment is mandatory. The acceptance of the term and the consequent compliance to the provisions of the settlement constitute neither the confession to the facts nor the recognition of the illicit nature of investigated conduct. A total number of 405 terms were approved by the regulatory body between 2009 and 2014, which characterizes a wide use of this regulatory instrument. This present analysis concluded that, although the settleement herein presented may be recognized as an important mechanism in the context of capital market regulation, its excessive use constitutes a distortion of both its purposes and of the foundations of normative discipline of the market, and even of the set of functions assigned to CVM.